2018
DOI: 10.1093/ibd/izy289
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Very Early-Onset Inflammatory Bowel Disease with Interleukin-10 Signaling Deficiency: Based on a Large Cohort Study

Abstract: Our study expands the current knowledge on the genotype-correlated phenotypes with a defect of IL10 signaling. B-cell lymphoma was more frequent than would be expected in patients with IL10RB mutations. There may be a unique genetic architecture among Eastern Asia compared with other populations. Although allogeneic HSCT represents a causal therapeutic approach for IL10-and IL10R-deficient patients, a word of caution is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 40 publications
2
51
0
1
Order By: Relevance
“…Since the initial report patients with IL10R signaling defects in 2009 by Glocker et al [8], more than 130 VEO-IBD patients with IL-10 or IL-10R gene mutations have been reported [10,11]. Most patients were from Europe and Asian, where IL-10R mutations were more frequent than IL-10 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial report patients with IL10R signaling defects in 2009 by Glocker et al [8], more than 130 VEO-IBD patients with IL-10 or IL-10R gene mutations have been reported [10,11]. Most patients were from Europe and Asian, where IL-10R mutations were more frequent than IL-10 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, VEO-IBD patients with IL-10RA mutations suffered from even more complicated, severe, and intractable disease. They were characterized by very early onset symptoms, common perianal diseases (abscess, stulas, ssure, skin tag) and extra-intestinal manifestations, such as skin rash and oral ulcers, respond poorly to traditional treatment, and high surgery rate and mortality [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, their colonic tissues are affected, accompanied by multiple perianal diseases. These, together with resistant to standard medical therapies, lead to a high mortality in China ( Huang et al, 2017 ; Zheng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord blood is a rich source of hematopoietic stem cells, and umbilical cord blood transplantation (UCBT) has been used for treatment of malignant and nonmalignant diseases to re-establishment of the hematopoietic system and correct immunodeficiency ( Frassoni et al, 2003 ; Munoz et al, 2014 )._ENREF_5 Previous studies have shown that UCBT with reduced-intensity conditioning has represented a curable treatment for patients with IL10RA -associated immune deficiency, making it a potential treatment for IBD ( Uhlig and Muise, 2017 ; Ye et al, 2017 ; Peng et al, 2018 ; Zheng et al, 2019 ). Unfortunately, some IBD patients with IL10RA deficiency fail to achieve successful engraftment after the UCBT,_ENREF_3 limiting the application of UCBT in IBD patients ( Zheng et al, 2019 ). However, the impact of defective IL10 signaling on human intestinal inflammation has not been clarified ( Glocker et al, 2009 ; Zheng et al, 2019 ) and little is known on risk factors associated with engraftment failure after the UCBT in IBD patients with IL10RA deficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation